2016
DOI: 10.1186/s12929-016-0302-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential humoral and cellular immunity induced by vaccination using plasmid DNA and protein recombinant expressing the NS3 protein of dengue virus type 3

Abstract: BackgroundThe dengue non-structural 3 (NS3) is a multifunctional protein, containing a serine-protease domain, located at the N-terminal portion, and helicase, NTPase and RTPase domains present in the C-terminal region. This protein is considered the main target for CD4+ and CD8+ T cell responses during dengue infection, which may be involved in protection. However, few studies have been undertaken evaluating the use of this protein as a protective antigen against dengue, as well as other flavivirus. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The generation of both cell-mediated and NAb responses against DENV3 increased substantially (Versiani et al, 2017). Hurtado-Melgoza et al reported that the DNA vaccine candidate targeting DENV3 NS3 triggered a favorable response with the activation of T lymphocytes; however, immunization with this DNA vaccine presented no detectable antibody titers against DENV3 (Hurtado-Melgoza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of both cell-mediated and NAb responses against DENV3 increased substantially (Versiani et al, 2017). Hurtado-Melgoza et al reported that the DNA vaccine candidate targeting DENV3 NS3 triggered a favorable response with the activation of T lymphocytes; however, immunization with this DNA vaccine presented no detectable antibody titers against DENV3 (Hurtado-Melgoza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This response was of low magnitude, especially when compared to the recombinant protein vaccine in which antibody titers were 320 times higher. These results suggested that mice immunized with the gene coding for the NS3-DEN3 protein are primed to develop a Th1 response which provide protection against infection with dengue virus 12 .…”
mentioning
confidence: 94%
“…Having a vaccine against the four strains of DENV which is safe, effective and affordable will be a breakthrough for disease control. This was one of the main triggers of the work of Hurtado-Melgoza et al 12 . First, we would have to consider that DENV infection induces potent innate immune responses, which in turn shape the adaptive immune responses, including not only B cell humoral responses with antibody production but also cellular responses mediated by CD4+ and CD8+ T cells 13 .…”
mentioning
confidence: 99%
“…Non-structural proteins play important role in viral infection, viral replication and proliferation, pathogenesis and immune evasion (Schierhorn et al, 2017). Some viral non-structural proteins have been considered as virulence factors (DeDiego et al, 2016), vaccine candidates (Hurtado-Melgoza et al, 2016;Kitagawa et al, 2017;Reyes-Sandoval and Ludert, 2019) and major targets for antiviral therapy (Chu et al, 2017). However, functions of GCRV non-structural proteins are not well understood.…”
Section: Introductionmentioning
confidence: 99%